2020
DOI: 10.3390/ijerph17197156
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Circadian Rhythm Disruption on Mental Health and Physiological Responses among Shift Workers and General Population

Abstract: Background: The effect of circadian disruption on the bio-psychological clock system has been widely studied. However, the mechanism and the association of circadian rhythm disruption with mental health and physiological responses are still unclear. Therefore, this study was conducted to investigate the effects of circadian rhythm disruption on mental health and physiological responses among shift workers and the general population. Methods: A total of 42 subjects participated in this quasi-experimental study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Continuously disturbing the entrainment of endogenous circadian rhythms with external diurnal Zeitgeber rhythms with can weaken the regenerative ability of the organism ( 3 , 4 ). Night work is associated with negative consequences for somatic and mental health ( 5 ) and persistent desynchronization of endogenous rhythms limits cognitive performance ( 6 ). Thus, with the increase in flexible working times, innovative lighting concepts that take particular account of non-visual lighting effects become particularly important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuously disturbing the entrainment of endogenous circadian rhythms with external diurnal Zeitgeber rhythms with can weaken the regenerative ability of the organism ( 3 , 4 ). Night work is associated with negative consequences for somatic and mental health ( 5 ) and persistent desynchronization of endogenous rhythms limits cognitive performance ( 6 ). Thus, with the increase in flexible working times, innovative lighting concepts that take particular account of non-visual lighting effects become particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…6. People vary in their preferences for lighting; conventional good practice is to offer individual control but this can negate the circadian effects.…”
mentioning
confidence: 99%
“…Recognition of current time is one of the most important cognitive skills for human life. If a person lives without clocks, their circadian rhythm can be disrupted, and this can result in various kinds of mental problems [ 3 ]. Particularly, circadian rhythm disruptions are common in older people and are more severe in people with dementia [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This rhythm refers to 24-hour cycle that is observed in many physiological variables (e.g., heart rate [17]) driven by exogenous cycles of light and darkness, temperature, and sleep-wake cycle, to name a few [18]. Circadian rhythms have been reported to be an important factor in mental health, alertness and human performance [19], with disruptions causing significant effects on mood, processing speed, and working memory [20], as well as anxiety and depression [21]. Recent research has shown that this rhythm can be quantified with wearable devices [22], thus further pushing for a complete wearable solution.…”
Section: Introductionmentioning
confidence: 99%